Chemical characterization of BiFeO3 obtained by Pechini method - Ferri,Elídia A. Vetter (2008)
This work describes the synthesis and characterization of BiFeO3 obtained by the Pechini route using bismuth nitrate and iron nitrate as precursors. The powders were annealed at 800 °C in air for 2 h. X-ray diffraction patterns showed that the material presents two phases, BiFeO3 (95%) and α-Bi2O3 (5%). The ferroelectric transition of the sample at 821 °C was detected by differential thermal analysis. Results of analyses by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and energy dispersive X-ray fluorescence (EDX) showed that the sample is chemically homogeneous. Transmission electron microscopy images revealed that the sample is uniform and contains spherical particles with an average size of 30 nm.